2010
DOI: 10.1073/pnas.0910200107
|View full text |Cite
|
Sign up to set email alerts
|

Systematic discovery of nonobvious human disease models through orthologous phenotypes

Abstract: Biologists have long used model organisms to study human diseases, particularly when the model bears a close resemblance to the disease. We present a method that quantitatively and systematically identifies nonobvious equivalences between mutant phenotypes in different species, based on overlapping sets of orthologous genes from human, mouse, yeast, worm, and plant (212,542 gene-phenotype associations). These orthologous phenotypes, or phenologs, predict unique genes associated with diseases. Our method sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
280
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(291 citation statements)
references
References 38 publications
(36 reference statements)
7
280
1
1
Order By: Relevance
“…41,43 Although the similarities between human and model organism mutant phenotype can be informative, this approach may miss numerous opportunities in which the protein functions are part of conserved pathways among organisms when the orthologous phenotypes are not obviously analogous. 44 For example, a yeast model for angiogenesis 44 and a worm model for breast cancer 44 revealed molecular pathways that contribute to these disorders based on the ''phenology'' concept. Therefore, we adapted a gene-centric rather than phenotypic-centric approach to study gene function by integrating model organism and human data in a single aggregated web-based resource.…”
Section: Discussionmentioning
confidence: 99%
“…41,43 Although the similarities between human and model organism mutant phenotype can be informative, this approach may miss numerous opportunities in which the protein functions are part of conserved pathways among organisms when the orthologous phenotypes are not obviously analogous. 44 For example, a yeast model for angiogenesis 44 and a worm model for breast cancer 44 revealed molecular pathways that contribute to these disorders based on the ''phenology'' concept. Therefore, we adapted a gene-centric rather than phenotypic-centric approach to study gene function by integrating model organism and human data in a single aggregated web-based resource.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic mapping research has identified many genes and pathways involving these genes that are responsible for phenotypic outcomes. However, in many cases, the specific genes responsible for the phenotypes may not be conserved between species, 43,44 or even between strains of the same species; however, the pathways perturbed are often conserved across millions of evolutionary years. This suggests that rather than focusing on specific genetic alterations or expression changes in a single gene, research could benefit from considering data at a higher, so called ' systems ' level.…”
Section: The Need To Examine Pathways Not Just Individual Genes To mentioning
confidence: 99%
“…Proteins sharing a particular functional category cluster in the same location of PPI networks, and are referred to as functional modules, and placement of proteins in PPI networks can be used to inform protein function prediction studies (Dziembowski & Seraphin, 2004;Yook et al, 2004;Makino & Gojobori, 2006). Understanding networks of PPIs can be used to predict additional genes that, when mutated, may cause the same disease as that associated with mutations in interacting partners (McGary et al, 2010), and also explains why so many different mutated genes can cause the same or similar complex disease (Bill & Geschwind, 2009;Bourgeron, 2009;Crespi et al, 2010;Gilman et al, 2011;Guilmatre et al, 2009). Relating to the network-based nature of many gene products is the concept that some proteins interact with multiple other proteins, referred to as 'hub' genes (Fig.…”
Section: Network Studies To Leverage Functional Predictionmentioning
confidence: 99%
“…The reason why model organisms are able to contribute so effectively to our understanding of human diseases lies in the high degree of molecular conservation found between metazoan species, and in the conserved nature of protein-protein, and other, networks (Gandhi et al, 2006). Indeed, even bacteria, plants, protists, and fungi are being exploited to explore differing aspects of biology relevant to human disease (Annesley & Fisher, 2009;Ilievska et al, 2011;McGary et al, 2010;Spradling et al, 2006). …”
Section: Role Of Animal Modelsmentioning
confidence: 99%